Active Noise Control for Noise Generated by Electric Vehicle HVAC Systems Using Virtual Sensing - Taisei Kusano; Koki Shige; Tatsuya Inoue; Yuta Oba; Naoyuki Takeda; Osamu Terashima; Shuho Yamada (International Journal of Automotive Engineering)
This study focuses on reducing noise generated by heating, ventilation, and air conditioning (HVAC) systems in electric vehicles to enhance in-cabin comfort. To achieve this, we employed feedback active noise control (ANC) with a real-time filter update in the frequency domain. A novel control algorithm was developed using a sliding discrete Fourier transform for each sample, along with a gradient descent method for noise adaptation in the frequency domain. Numerical analysis first confirmed the effectiveness of the feedback control (FB) approach, and subsequent experiments were conducted on a commercial electric vehicle. A microphone installed on the map lamp was used to reference the noise generated by the air conditioner. The experimental results demonstrated that feedback control reduced noise by approximately 3.0 dB (O.A. [A]) in the 20–200 Hz frequency band, showing significant potential for improving vehicle quietness.